Education Game based on Timor Local Wisdom as an Android-Based Mathematics Learning Media - Suddin, Sulasri; Deda, Yohanis Ndapa (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
The linkage of technology in the world of education today has developed rapidly. One of them is the development of mathematics learning media in the form of educational games. The purpose of this research is to develop an educational learning media game that is integrated into Timor local wisdom so that this media has its uniqueness to help students learn. Research on a fast educational game on mathematics based on an android smartphone was conducted at MTs Nurul Falah, Kefamenanu, NTT. The media was developed using software construct 2. The method used in this research is development research with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of the validity test based on material experts, media experts, and teachers indicate that educational games with the theme of local wisdom as android-based mathematics learning media were included in the category of very feasible to use with an average validation of 4.33 and very feasible criteria. At this stage, a limited trial using a questionnaire showed that game education received a positive response to the use of game education media with an average percentage of 98.93%. These results indicate that the process of learning mathematics using this media can motivate and facilitate student learning compared to the learning that has been done. During the pandemic, COVID-19 media can be used as online-based learning media because students can easily download the application then the teacher controls the process.